2016
DOI: 10.1111/jvs.12447
|View full text |Cite
|
Sign up to set email alerts
|

Recent changes in alpine vegetation differ among plant communities

Abstract: Aim Reports on recent changes in high‐mountain vegetation are mostly based on re‐surveys of mountaintop floras. Summits are very specific habitats, however, and detected trends may not necessarily represent alpine vegetation in general. Here, we analyse re‐samples of three prevalent plant communities in non‐summit alpine habitats (snowbeds, two grassland types). Location Northeastern European Alps. Methods In 2013 we re‐sampled a total of 91 relevés of three plant communities from the 1990s. We compared origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 47 publications
0
22
2
Order By: Relevance
“…While modeling studies have predicted considerable lags in the future response of Alpine plants to climate warming 15 , empirical data about dynamics of the recent past appear contradictory. Some studies concluded that mountain vegetation follows climate almost without delay 5,17 , whereas other results indicated considerable inertia, especially in case of subalpine and alpine grassland vegetation 31,32 . Importantly, most empirical analyses available so far took a ‘community perspective’, i.e., they analyzed how local assemblages of plants have reacted to climate change in terms of attributes like species richness or composition 5,17 .…”
Section: Discussionmentioning
confidence: 99%
“…While modeling studies have predicted considerable lags in the future response of Alpine plants to climate warming 15 , empirical data about dynamics of the recent past appear contradictory. Some studies concluded that mountain vegetation follows climate almost without delay 5,17 , whereas other results indicated considerable inertia, especially in case of subalpine and alpine grassland vegetation 31,32 . Importantly, most empirical analyses available so far took a ‘community perspective’, i.e., they analyzed how local assemblages of plants have reacted to climate change in terms of attributes like species richness or composition 5,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our results suggest that montane grasslands may be less resistant to periods of water scarcity than grasslands of high, alpine elevation. Alternatively, as longlived and clonal species inhabit plant communities of high, alpine elevation, they could be particularly slow in response to changing environments (Dullinger et al 2012;Gritsch, Dirnböck, and Dullinger 2016).…”
Section: Initial Aboveground Biomass Response To Abrupt Warmingmentioning
confidence: 99%
“…In the mountainous regions, the degree of climate driven changes can vary significantly even within a single mountain range (Gritsch et al 2016). This means that the nature, intensity, and frequency of climate change may be redistributed from one to the next spatial scale, and therefore, may not act uniformly across specific vegetation types and landscapes (Garcia et al 2014).…”
Section: Environmental Changes and Responses Of Mountain Vegetationmentioning
confidence: 99%